2012
DOI: 10.1002/ar.22439
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mesterolone on Satellite Cell Distribution and Fiber Morphology within Maturing Chicken Pectoralis Muscle

Abstract: Mesterolone is a synthetic oral anabolic androgenic steroid used to treat hypogonadism. There are frequent reports of mesterolone abuse in human and equine sports to increase muscle mass and strength. However, limited information is available about how this drug exerts its effects on skeletal muscle. Satellite cells (SCs) are mononuclear myogenic stem cells that contribute to postnatal muscle growth and repair. As SC activation and subsequent differentiation to new myonuclei is a major event during muscle hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 90 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…4 SCs are mononuclear cells located between the basal lamina and plasmalemma of the skeletal muscle fiber. 3,5 These cells induce muscle growth either by fusing to preexisting myofibers (hypertrophy) or, less commonly, by fusing together to form new myofibers (hyperplasia). [5][6][7] Surprisingly, studies on non-SCs were the first to reveal the molecular mechanisms of the myogenic program.…”
Section: Historical Viewmentioning
confidence: 99%
See 2 more Smart Citations
“…4 SCs are mononuclear cells located between the basal lamina and plasmalemma of the skeletal muscle fiber. 3,5 These cells induce muscle growth either by fusing to preexisting myofibers (hypertrophy) or, less commonly, by fusing together to form new myofibers (hyperplasia). [5][6][7] Surprisingly, studies on non-SCs were the first to reveal the molecular mechanisms of the myogenic program.…”
Section: Historical Viewmentioning
confidence: 99%
“…3,5 These cells induce muscle growth either by fusing to preexisting myofibers (hypertrophy) or, less commonly, by fusing together to form new myofibers (hyperplasia). [5][6][7] Surprisingly, studies on non-SCs were the first to reveal the molecular mechanisms of the myogenic program. At first, it was noticed that fraction of fibroblast cell line (C3H 10T1/2) was transformed into myogenic lineage cells after being treated with an anti-neoplastic nucleoside analogue, 5-Azacytidine.…”
Section: Historical Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that mesterolone significantly increases the weight and fiber size of the soleus muscle of transgenic mice 15 . We found that oral administration of mesterolone significantly increases the number of SCs in maturing avian pectoralis, a response accompanied by increased myonuclear density and DNA content 12 . However, it is unclear if mesterolone has distinct effects on different types of normal adult muscle fibers.…”
Section: Introductionmentioning
confidence: 71%
“…Among the various stimuli promoting SC activity are anabolic androgenic steroids (AASs), which also augment muscle mass and size 4 , 5 , 12 . Mesterolone (17-beta-hydroxy-1 alpha-methyl-5 alpha-androstan-3-one) is one of the most frequently used exogenous AASs for the treatment of hypogonadism 12 , 13 . Mesterolone is distinguished from other AASs by its unique chemical structure that does not undergo ring aromatization into estrogen therefore it has no estrogenic side effects.…”
Section: Introductionmentioning
confidence: 99%